Research Software: A Key (Neglected) Component of the Digital Research Infrastructure Ecosystem - van der Walt, Anelda; Martin, Kim; Panji, Sumir; Trusler, Angelique; Vaccari, Mattia; Van Heusden, Peter (Preprint, 2025)
Technological advances have elevated the importance of digital research infrastructure across the research lifecycle. The growing complexity of the digital research infrastructure ecosystem gave rise to new standards, practices, and job roles requiring unique and specialised skill sets. Research software is a critical component of this ecosystem. Despite the proliferation of research software initiatives across all disciplines in South Africa, a decade-old global movement to study and advocate for research software and its developers has largely been overlooked locally, resulting in missed opportunities. By actively engaging in international research software efforts, South Africa can benefit significantly and contribute meaningfully.
Keywords: research software; computing and data infrastructure; open science; funding; policy development